PERCEPTION OF ELEMENTARY SCHOOL TEACHERS AND STUDENTS ON DIGITAL AUGMENTED REALITY LEARNING MEDIA - dudu suhandi saputra (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the extent to which teachers and elementary school students perceive the use of augmented reality digital learning media. The method used in this research is the descriptive qualitative research method. The results of this study say that learning using augmented reality is very suitable for use at the elementary school level. Because basically the learning of elementary school children is still teacher-centered and the use of learning media itself is still minimally used. There are still many teachers who lack an understanding of science and technology. The teacher's perception of the impact of augmented reality is that by utilizing technology, students not only gain cognitive abilities, but students also gain the abilities and skills in using and utilizing technology wisely which is one of the skills in the 21st century. Furthermore, students' perceptions of media Augmented reality digital learning is that students can enjoy learning, enrich their knowledge of the material studied through augmented reality, and students are more enthusiastic about learning. Augmented reality is a learning media by utilizes technological developments.